140 Development of an Online Educational Initiative to Engage Beef Stakeholders in a Global Scale. (8th March 2022) - Brandão, Alice; Cooke, Reinaldo F; Lamb, G Cliff C; Dunlap, Kathrin; Pohler, Ky G
Abstract: The objective of this educational initiative (International Beef Cattle Academy; IBCA) was to present translational research-driven content regarding beef production to international stakeholders. The methodology for development of the IBCA program included: 1) determination of content courses (n = 7); 2) assignment of faculty members as content creators and instructors (n = 11), general coordinator (n = 1) and associate coordinators (n = 2); 3) selection of participants from applicant pool using a rubric designed to create an inclusive and diverse learning community of international industry leaders. Course structure and content delivery remained consistent across all courses. Asynchronous lectures were delivered via a LMS (D2L), and weekly, hour-long synchronous remote meetings for participants were hosted by instructors. Within courses, content was distributed to yield 3.49 ± 0.41 h of recorded material per week. Automatically graded quizzes with multiple attempts allowed, were utilized as formative assessments and mechanism for control of content release. Access to subsequent topics was granted when the quiz score was of 80% or above. At the end of each program cycle (11 months) an optional experiential learning opportunity was offered. Participants were invited to a week-long instructor supervised workshop in which they took part in hands-on practicums as well as field trips. After 3 full cycles, qualitative analysis of participant feedback given in the form of interviews (n = 19) has generated emergent themes of learning environment satisfaction and successful adoption/application of new technologies. Interaction during the live synchronous sessions and the applicability of the content were amongst the positive aspects according to participant feedback. Based on these interviews, the IBCA successfully met the objective of improving knowledge and adoption of research-based technologies through content delivery and learning community creation for beef industry stakeholders from 14 different countries (USA, Canada, Brazil, Romania, Kazakhstan, Mexico, Panama, Dominican Republic, Germany, South Africa, Zimbabwe, Turkey, Australia, Pakistan).